Pengembangan Alat Evaluasi Pembelajaran Menggunakan Quizizz Pada Mata Pelajaran Biologi Kelas XI di SMAN 6 Sinjai - Nasrun, A. Nidaul Magvira; Febriati, Farida; H, Nurhikmah (Peneliti.net, 2024)
In order to better and more advanced education, there is a need forimproved learning and evaluation processes, because from the evaluationresults can be seen the level of success or failure in an educational process.This research uses research and development methods (R&D). Thisresearch is aimed at 1) Identifying the need for development of evaluationtools using quizizzz on Biology Class XI courses in SMAN 6 Sinjai. 2) Todescribe the design of learning evaluation tool using quizizz on biologylessons Class XI in SMan 6 Sinai. 3) Measuring the level of validity ofteaching evaluation instruments using Quiziz on Biological courses ClassXI at SMAN 6. The subjects of this study are 20 students, 1 teacher, and 2validators consisting of material/fill validators and media validators. Datacollection using interviews, material/full validation lifts, media validationhangs, student test/response lifts and teacher assumptions lifts. The resultsof this study are: 1) the results of the needs analysis stated that thedevelopment of evaluation tools using quizizz apication is required. 2) theresults validation of the material expert is on criteria very valid. 2)validation results by the media expert obtained with criteria highly valid.3) the results raise the responses of students and teachers are in the categoryof qualifying to use. 4) the test results of subjects in category qualified.Based on the results of this research, it can be concluded that the productsthat have been developed by the researchers have a valid validity level andqualify for use in the defence evaluation process in SMAN 6 Sinjai